Aesthetic dissonance. On behavior, values, and experience through new media - Mróz, Adrian (Hybris, 2019)
Aesthetics is thought of as not only a theory of art or beauty, but also includes sensibility, experience, judgement, and relationships. This paper is a study of Bernard Stiegler’s notion of Aesthetic War (stasis) and symbolic misery. Symbolic violence is ensued through a loss of individuation and participation in the creation of symbols. As a struggle between market values against spirit values human life and consciousness within neoliberal hyperindustrial society has become calculable, which prevents people from creating affective and meaningful attachments to symbols in relation to our retentional apparatuses, technology and memory. Such tension can be thought of as a dissonance between overlapping domains of social life, private and public. New Media is a reflection of aesthetic dissonance, an experience such as being bored and entertained at the same time, between antagonistic experiences, values, and behavior. Moreover, new media is at once a medium of customizing aesthetic experience individually as well as the threat and practice of prioritizing calculability and modeling of consumer behavior in favor of capitalistic effectiveness, which results in the simultaneous categorization of an individual as a data point, putting those who do not fit an algorithm’s premises at a disadvantage.